Tourism Potential of Protected Natural Areas and Problems of Its Use (Texas Journal of Multidisciplinary Studies, 2022)
The use of the ecotourism potential of protected natural areas for the purpose of organizing ecotourism has been a global trend for many years. The article describes the key aspects of the development of ecological tourism in protected natural areas.